Associations between serum trace elements and the risk of nasopharyngeal carcinoma: a multi-center case-control study in Guangdong Province, southern China - Ge, Xin-Yu; Xie, Shang-Hang; Wang, Hao; Ye, Xin; Chen, Wenjie; Zhou, Hang-Ning; Li, Xueqi; Lin, Ai-Hua; Cao, Su-Mei (Frontiers in Nutrition, 2023)
Abstract BACKGROUND: Associations between trace elements and nasopharyngeal carcinoma (NPC) have been speculated but not thoroughly examined. METHODS: This study registered a total of 225 newly diagnosed patients with NPC and 225 healthy controls matched by sex and age from three municipal hospitals in Guangdong Province, southern China between 2011 and 2015. Information was collected by questionnaire on the demographic characteristics and other possibly confounding lifestyle factors. Eight trace elements and the level of Epstein-Barr virus (EBV) antibody were measured in casual (spot) serum specimens by inductively coupled plasma–mass spectrometry (ICP-MS) and enzyme-linked immunosorbent assay (ELISA), respectively. Restricted cubic splines and conditional logistic regression were applied to assess the relationship between trace elements and NPC risk through single- and multiple-elements models. RESULTS: Serum levels of chromium (Cr), cobalt (Co), nickel (Ni), arsenic (As), strontium (Sr) and molybdenum (Mo) were not associated with NPC risk. Manganese (Mn) and cadmium (Cd) were positively associated with NPC risk in both single- and multiple-element models, with ORs of the highest tertile compared with the reference categories 3.90 (95% CI, 1.27 to 7.34) for Mn and 2.30 (95% CI, 1.26 to 3.38) for Cd. Restricted cubic splines showed that there was a linear increasing trend between Mn and NPC risk, while for Cd there was a J-type correlation. CONCLUSIONS: Serum levels of Cd and Mn was positively related with NPC risk. Prospective researches on the associations of the two trace elements with NPC ought to be taken into account within the future.